Liquid thermal diffusion in a batch rotary column - Bott, T. R. (1978)
Experimental observations of separation by thermal diffusion in rotary columns have been published, but no adequate theory to explain the column performance has been given. By consideration of the hydrodynamics within the annular space an approximate theory has been developed which shows that for a geometrically perfect column the relevant parameters affecting separation can be simply related to the corresponding static column. The relaxation-time and separation are virtually independent of the speed of rotation and separation values are more favourable for the rotary column. The application of the theory to non-perfect practical columns requires the consideration of the "equivalent annulus width" concept similar to the static case. Experimental tests conducted at different speeds of rotation in two geometrically different columns whose inner cylinder rotates and the outer is static, showed that the rotation at moderate speeds increased the equilibrium separation by about 7%, reducing, simultaneously the relaxation time by an average of 3%. These results are in good agreement with the theoretical predictions.